Integration of Vocational Education and Multistakeholder Collaboration in West Java Province's Disaster Mitigation - Nugraheni, Dwi; Saragih, Herlina Juni Risma; Kusuma (International Journal of Technology and Education Research, 2025)
West Java Province has a high risk of disasters due to complex geological conditions, population density, and rapid urbanisation. These conditions require a paradigm shift from reactive mitigation strategies to proactive and integrated ones. This study aims to analyse the integration between vocational education in disaster management and multi-stakeholder collaboration as a strategic effort to strengthen the disaster mitigation system in West Java. Using a qualitative-descriptive method through literature review and Focus Group Discussion (FGD) with relevant stakeholders, this study examines the roles and synergies within the Pentahelix model framework. Research findings indicate that vocational education in disaster management, with a practice-based learning approach (learning by doing), plays a strategic role in producing technically competent and adaptive human resources. On the other hand, the Pentahelix collaboration model, which involves the government, academics, the business world, communities, and the media, creates a comprehensive and inclusive mitigation ecosystem. The integration of these two aspects facilitates the transfer of field knowledge, scientific-policy collaboration, and increased collective awareness. This synergy produces an adaptive resilience ecosystem that bridges academic science, field practice, and community empowerment. This study concludes that strengthening cross-sector coordination, expanding the implementation of applied research, directing CSR towards mitigation activities, and optimising the media as an educational channel are key to realising a sustainable and collaborative disaster mitigation model in West Java.